Analisis Strategi Pemasaran Digital (Digital Marketing) dalam Meningkatkan Daya Saing PT Pos Indonesia (Persero) Padang Melalui Layanan Pospay - Brilliansyah, Eko; Salfadri, Salfadri; Yulistia, Yulistia (Fakultas Ekonomi, Universitas Ekasaktii, 2024)
With the passage of legislation No. 38 of 2009, PT Pos Indonesia experienced quite tight competition with its competitors in all areas of services offered by PT Pos Indonesia to its customers, especially in the field of financial services. The emergence of digital-based start-ups. Meanwhile, PT Pos Indonesia, which plays the role of PPOB (Payment Point Online Bank), known as the Pospay service, has not used Digital Marketing technology. With this problem, PT Pos Indonesia issued or introduced a digital-based Pospay service system in early 2019, which was based on Fintech to increase the company's competitiveness. Therefore, This Study aims to :(1) determine the internal factors (strengths and weaknesses) of pospay: (2) Knowing the external factors (opportunities and threats) owned by Pospay: (3) Knowing Pospay's digital marketing strategy to increase the competitiveness of PT Pos Indonesia (Persero) Padang. Data processing using IFAS analysis to analyze internal factors, EFAS analysis for external factors. Once entered into the quantitative model, namely the SWOT matrix which is based on primary data from the results of research that is Field Research using a structured questionnaire directly to 88 samples. Where The results of the analysis using IFAS and EFAS and using SWOT analysis show that the recommended digital marketing strategy for PT Pos Indonesia (Persero) Padang to increase competitiveness through Pospay services is the SO Strategy.